Membrane charge primes the necroptotic kinase RIPK3 for amyloid assembly - Fátima C. Escobedo-González; Andrea Gelardo; Alexandra Reimers; Paula Polonio; Miguel Mompeán; Gustavo A. Titaux-Delgado (Communications Chemistry)
Abstract Receptor-interacting protein kinase 3 (RIPK3) drives necroptosis by assembling into functional amyloid fibrils. Here we show that lipids modulate RIPK3 amyloidogenesis by stabilizing an aggregation-prone intermediate. While electrostatic repulsion maintains RIPK3 in a soluble state, charge compensation alone is not sufficient for fibril formation and hydrophobic contacts are required to initiate nucleation. Using solution-state NMR, fluorescence-based assays and polymer-encased lipid particles, we demonstrate that negatively charged membranes selectively recruit RIPK3 and restrict its conformational flexibility, accelerating aggregation. These findings reveal a membrane-guided mechanism for RIPK3 assembly and suggest that lipid surfaces, like those implicated in pathological amyloid formation, may modulate functional amyloidogenesis even in the absence of canonical necroptotic stimuli.